Revision as of 06:34, 9 August 2010 by imported>Johan Förberg
In elementary algebra, the binomial theorem or the binomial expansion is a mechanism by which expressions of the form
can be expanded. It is the identity that states that for any non-negative integer n,
![{\displaystyle (x+y)^{n}=\sum _{k=0}^{n}{n \choose k}x^{k}y^{n-k},}](https://wikimedia.org/api/rest_v1/media/math/render/svg/a373be626cc84c1a74fb0e6df074fe5247a20775)
where
![{\displaystyle {n \choose k}={\frac {n!}{k!(n-k)!}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/420bf080448b0b64ddd2eaeaa6a9c2cb8fd6923b)
is a binomial coefficient. Another useful way of stating it is the following:
Pascal's triangle
An alternate way to find the binomial coefficients is by using Pascal's triange. The triangle is built from apex down, starting with the number one alone on a row. Each number is equal to the sum of the two numbers directly above it.
n=0 1
n=1 1 1
n=2 1 2 1
n=3 1 3 3 1
n=4 1 4 6 4 1
n=5 1 5 10 10 5 1
Thus, the binomial coefficients for the expression
are 1, 3, 6, 4, and 1.
Proof
One way to prove this identity is by mathematical induction.
Base case: n = 0
![{\displaystyle (x+y)^{0}=\sum _{k=0}^{0}{0 \choose k}x^{0-k}y^{k}=1}](https://wikimedia.org/api/rest_v1/media/math/render/svg/4deabc01149a6174a16a1587235a528e2e9fe9e3)
Induction case: Now suppose that it is true for n :
and prove it for n + 1.
![{\displaystyle (x+y)^{n+1}=(x+y)(x+y)^{n}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/a53cc3f59e822c5b9abb376bdc91244f4047ea44)
![{\displaystyle =(x+y)\sum _{k=0}^{n}{n \choose k}x^{n-k}y^{k}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/d062b7acbd62f0af84d8fbf8592052a7fde627a8)
![{\displaystyle =\sum _{k=0}^{n}{n \choose k}x^{n+1-k}y^{k}+\sum _{j=0}^{n}{n \choose j}x^{n-j}y^{j+1}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/c18bb67df82e28bb9077f0d9bc692eed0c2b2d03)
![{\displaystyle =\sum _{k=0}^{n}{n \choose k}x^{n+1-k}y^{k}+\sum _{j=0}^{n}{n \choose {(j+1)-1}}x^{n-j}y^{j+1}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/4fe772930187e36d239c2617a3a5532c8eacede0)
![{\displaystyle =\sum _{k=0}^{n}{n \choose k}x^{n+1-k}y^{k}+\sum _{k=1}^{n+1}{n \choose {k-1}}x^{n+1-k}y^{k}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/192d1ff71de8fc67f3307b37a9034a3f4bd11d63)
![{\displaystyle =\sum _{k=0}^{n+1}{n \choose k}x^{n+1-k}y^{k}-{n \choose {n+1}}x^{0}y^{n+1}+\sum _{k=0}^{n+1}{n \choose {k-1}}x^{n+1-k}y^{k}-{n \choose {-1}}x^{n+1}y^{0}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/96cc74454f9f1c1a1ada8d037c93c6a24fb14f54)
![{\displaystyle =\sum _{k=0}^{n+1}\left[{n \choose k}+{n \choose {k-1}}\right]x^{n+1-k}y^{k}\,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/c1f147a519a0c6ba20e962b554bbfb0268d8424b)
![{\displaystyle =\sum _{k=0}^{n+1}{{n+1} \choose k}x^{n+1-k}y^{k},}](https://wikimedia.org/api/rest_v1/media/math/render/svg/6bc4a58b294d83618b7005cf05d9ca057e725595)
and the proof is complete.
Examples
These are the expansions from 0 to 6.
Newton's binomial theorem
There is also Newton's binomial theorem, proved by Isaac Newton, that goes beyond elementary algebra into mathematical analysis, which expands the same sum (x + y)n as an infinite series when n is not an integer or is not positive.